Myrmicinosporidium durum Hölldobler, 1933 (Fungi), an Ant endoparasite, in Slovenia - Espadaler, Xavier (Acta entomologica slovenica (Ljubljana), 2012)
The ant endoparasitic fungus Myrmicinosporidium durum is documented for Slovenia. It was detected in a major worker of Pheidole pallidula.
Keywords: Endoparasitic fungus; endoparazitske glive; Formicidae; Fungi; fungus; Hymenoptera; Myrmicinosporidium durum; Pheidole pallidula; Slovenia; Slovenija